CYBERBULLYING BEHAVIOR IN ADOLESCENTS A SOCIAL MEDIA USER - Windarwati, Heni Dwi; Saragih, Desi Christin; Merdikawati, Ayut; PH, Livana (Jurnal Ners Widya Husada, 2020)
Social media is a communication tool through online media to facilitate individuals to carry out social processes. The positive impact of social media can be very beneficial and bring good to its users, but if users are not controlled in using social media, users can harm themselves and other users, such as conducting cyberbullying to other social media users. The most social media users are adolescents. The research aims to find out the description of cyberbullying behavior in adolescents as social media users. Research with descriptive analytic type has been conducted on 126 adolescents in grade 10 senior high school in Malang. Data were collected using a cyberbullying behavior questionnaire consisting of 25 questions with a purposive sampling technique. Data were analyzed in a frequency distribution, the results showed 42.9% of respondents with high cyberbullying behavior and 57.1% of respondents with low cyberbullying behavior. This type of cyberbullying that is very often done in adolescents is sending harsh words to someone on social networks or chat rooms.